2018
DOI: 10.1371/journal.pone.0189699
|View full text |Cite
|
Sign up to set email alerts
|

“Every day they keep adding new tools but they don’t take any away”: Producing indicators for intermittent preventive treatment for malaria in pregnancy (IPTp) from routine data in Kenya

Abstract: BackgroundIntermittent preventive treatment for malaria in pregnancy (IPTp) is part of a multi-pronged strategy aimed at preventing malaria in pregnancy in areas of moderate to high transmission in sub-Saharan Africa. Despite being formally adopted as a malaria prevention policy over a decade ago, IPTp coverage has remained low. Recent demands for action have incorporated calls to strengthen IPTp monitoring and evaluation systems, including the use of routine data, to measure coverage, track implementation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…In addition to collecting RMNCAH health indicators, the system captures human resources, medicine, and logistics data. This data availability allows the health system to address broader contextual factors like human resource shortages or stock outs, which can act as hindrances to achieving high-quality RMNCAH data (15,29) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to collecting RMNCAH health indicators, the system captures human resources, medicine, and logistics data. This data availability allows the health system to address broader contextual factors like human resource shortages or stock outs, which can act as hindrances to achieving high-quality RMNCAH data (15,29) .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of an automated system in DHIS2 has been mentioned by studies in Africa. They found that the automated reporting system could minimize reporting time and increase the completeness and accuracy of MNCH data in their contexts (28,29) .…”
Section: Discussionmentioning
confidence: 99%
“…This data availability allows the health system to address broader contextual factors like human resource shortages or stock outs, which can act as hindrances to achieving high-quality RMNCAH data. (15,29) .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of automated system in the DHIS2 has been mentioned by the other African studies. According to those studies, the automated reporting system could minimize the reporting time and also increased the completeness and accuracy of MNCH data in their context (31,32) Although data accuracy and completeness remain an issue, users were encouraged to use DHIS2. To increase the use of DHIS2, MIS division of Bangladesh has started to announce and reward best performing district on annual basis.…”
Section: Discussionmentioning
confidence: 99%
“…This data availability allows the health system to address broader contextual factors like human resource shortages or stock outs, which can act as hindrances to achieving high-quality RMNCAH data. (15,32) .…”
Section: Discussionmentioning
confidence: 99%